2009
DOI: 10.1002/hlca.200800329
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Synthetic Chemistry, Chiral Separations, and Applications of Tröger's Base Analogues

Abstract: Trçgers base is a well-known chiral molecule with a few unusual structural features. The chemistry of Trçgers base analogues has been greatly developed over the last 20 years, and numerous interesting applications in supramolecular chemistry and in molecular recognition have emerged. This Review gives a short overview of the chemistry of Trçgers base and its analogues, with particular focus on recent achievements in synthesis, enantiomer separations, and applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(65 citation statements)
references
References 96 publications
(107 reference statements)
2
62
0
1
Order By: Relevance
“…These observations seemed auspicious, the expected reaction involving the substitution of a phosphine ligand by analogous carbene. However, after purification of the crude by column chromatograph on silica gel, 1 H-NMR and 13 C-NMR analyses performed on the white solid obtained revealed that we did not isolate the expected product. But it was a mixture of uncharacterized products.…”
Section: Thermolysis Tests Of Perhalogenated Adducts Of Tröger's Basementioning
confidence: 78%
See 2 more Smart Citations
“…These observations seemed auspicious, the expected reaction involving the substitution of a phosphine ligand by analogous carbene. However, after purification of the crude by column chromatograph on silica gel, 1 H-NMR and 13 C-NMR analyses performed on the white solid obtained revealed that we did not isolate the expected product. But it was a mixture of uncharacterized products.…”
Section: Thermolysis Tests Of Perhalogenated Adducts Of Tröger's Basementioning
confidence: 78%
“…Firstly, Tröger's base and its analogues (1a-d) were synthesized according to the method described in the litterature 13,15,18 . Thereafter, we proceeded on the removal of methylene bridge by using the method of Mahon 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, various of TB derivatives were synthesized and applied in the eld of molecular recognition [2], chiral ligands [3][4][5], DNA probes [6,7], stereo selective catalysis [8][9][10][11][12], drug development [13,14], CO 2 capture [15,16], bioorganic chemistry [17][18][19], electroluminescent materials [20,21] and supra molecular chemistry [22] in the last two decades. Their wide range of applications is based on their huge rigidity, V-shaped twisted con guration, N-central chirality and C 2 -symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…After this period the reaction mixture was cooled to 0ºC, sat. NH 4 Cl added and the mixture warmed to room temperature. The reaction mixture then diluted with CH 2 Cl 2 and the combined organic layers were then washed with brine, dried (Na 2 SO 4 ), filtered and the solvent removed in vacuo.…”
Section: General Methods For Monoalkylationmentioning
confidence: 99%